Leadership in a Changing World A Multidimensional Perspective - Mohiuddin, Muhammad; Khalid, Bilal; Samim Al Azad, Md; Ed-dafali, Slimane (Business, Management and Economics, 2022)
Leadership in a Changing World - A Multidimensional Perspective investigates the multi-dimensional aspect of leadership by exploring different perspectives and practices as well as existing theories of effective leadership in a changing world. Chapters address such topics as the connection between leadership, innovation, and creativity, venture leadership, e-leadership, digital leadership, and more. Beyond understanding the nature of effective leadership, this book examines the nature of leadership focusing on what we know and how we know it.